Prevention and management of chronic disease in Aboriginal and Islander Community Controlled Health Services in Queensland: a quality improvement study assessing change in selected clinical performance indicators over time in a cohort of services. Issue 4 (11th April 2013) - Panaretto, K S; Gardner, K L; Button, S; Carson, A; Schibasaki, R; Wason, G; Baker, D; Mein, J; Dellit, A; Lewis, D; Wenitong, M; Ring, I
Abstract : Objective: To evaluate clinical healthcare performance in Aboriginal Medical Services in Queensland and to consider future directions in supporting improvement through measurement, target setting and standards development. Design: Longitudinal study assessing baseline performance and improvements in service delivery, clinical care and selected outcomes against key performance indicators 2009–2010. Setting: 27 Aboriginal and Islander Community Controlled Health Services (AICCHSs) in Queensland, who are members of the Queensland Aboriginal and Islander Health Council (QAIHC). Participants: 22 AICCHS with medical clinics. Intervention: Implementation and use of an electronic clinical information system that integrates with electronic health records supported by the QAIHC quality improvement programme—the Close the Gap Collaborative. Main outcome measures: Proportion of patients with current recording of key healthcare activities and the prevalence of risk factors and chronic disease. Results: Aggregated performance was high on a number of key risk factors and healthcare activities including assessment of tobacco use and management of hypertension but low for others. Performance between services showed greatest variation for care planning and health check activity. Conclusions: Data collected by the QAIHC health information system highlight the risk factor workload facing the AICCHS in Queensland, demonstrating the need for ongoing support and workforce planning. Development of targets and weighting models is necessary to enable robust between-service comparisons of performance, which has implications for health reform initiatives in Australia. The limited information available suggests that although performance on key activities in the AICCHS sector has potential for improvement in some areas, it is nonetheless at a higher level than for mainstream providers. Implications: The work demonstrates the role that the Community Controlled sector can play in closing the gap in Aboriginal and Torres Strait Islander health outcomes by leading the use of clinical data to record and assess the quality of services and health outcome.